Pertumbuhan dan Produksi Kubis Bunga (Brassica oleracea var botrytis) dengan Sistem Pertanian Organik di Dataran Rendah - Widiatningrum, Talitha; Pukan, Krispinus Kedati (Biosaintifika: Journal of Biology & Biology Education, 2010)
The research aimed to compare caulifl ower growth and production planted at lowland and highland by using organic farming system. The research was single treatment experimentally, which was land height, consisted of highland (Kopeng) and lowland (Ambarawa). The variables were vegetative growth (leaves amount and plant weight) and generative development (fl ower initiation and fl ower weight). The data were analyzed by t-test. The result confi rmed that organic farming will make better lowland caulifl ower vegetative growth but least generative development compare to the highland one. It can be concluded that caulifl ower have the potency of being growth at lowland, even though with least yield.Keywords: lowland, highland, caulifl ower, organic